Effects of stocking density on growth and production in monoculture of Thai sharpunti (Barbonymus gonionotus) (Progressive Agriculture, 2017)
An experiment was carried out to study the density dependent growth of Thai sharpunti (Barbonymusgonionotus) for two months period. Three stocking densities such as 50/decimal, 100/decimal and 150/decimal representing treatment one (T1), treatment two (T2) and treatment three (T3), respectively were tested in three replications. A commercial diet (25% crude protein) was supplied twice daily throughout the study period up to satiation level. The total production of sharpunti was found 14.67 ± 2.05, 27.06 ± 3.09 and 36.87 ± 2.16 kg/decimal in T1, T2 and T3, respectively and they were significantly different (p